O ativismo judicial e a judicialização da vida : novos caminhos e paradigmas para a hermenêutica constitucional - Jiménez, Hugo Vinicius Castro (2013)
This Study, intended being accomplished, views, as an event, the judiciary power's challenges in Contemporaneity. One must take into account the fact that there is beyond an overburden concerning the above-mentioned power, here, in study, as well as a greater complexity in its lawsuits and so one demands from the Judiciary Power further than a differentiated and positive propense posture - one demands - dexterous instruments in order to confront postmodern society's new question's judicial liability and life judicialization function, derived from the abovementioned problematization, give, at the end, opportunity to a Constitution Judiciary Interpreter more careful Study whenever vindicated or not, so that this Study searches - tries - observing, beyond the controversy regarding to the new judicial posture whether it is favourable or not to the collectivity. First of all, one means finding out such a phenomenon and the role it develops in the so-called new constitutional construction. This present proposal consists in accurating the studies produced in doctrinal and academic level and verifying the phenomenology under allusion through jurisprudence and judged ones in proper annex.